208 Identification of Trichomonas vaginalis 5-nitroimidazole resistance targets to inform future drug development. (April 2022) - Graves, Keonte; Sharma, Jyoti; Reily, Colin; Tiwari, Hemant; Srinivasasainagendra, Vinodh; Secor, W. Evan; Novak, Jan; Muzny, Christina A.
Abstract : OBJECTIVES/GOALS: 5-nitroimidazoles are the only FDA-approved medications for T. vaginalis treatment. Resistance has been observed in 5-10% of cases, but may be rising. We aimed to delineate mechanisms of resistance in isolates of T. vaginalis using transcriptome profiling of resistant and sensitive T. vaginalis isolates. METHODS/STUDY POPULATION: T. vaginalis isolates (4 metronidazole (MTZ)-resistant were grown in triplicate in Diamond's Trypticase-Yeast-Maltose medium. MTZ susceptibility testing confirmed MTZ MLCs of T. vaginalis isolates. Total RNA extraction was done using Trizol reagent (Invitrogen; Carlsbad; CA); according to the manufacturer's instructions. RNA sequencing (RNAseq) and bioinformatics analyses were performed to identify significantly differentially expressed genes (DEGs) in MTZ-resistant vs. sensitive isolates. Subsequent qPCR was performed to confirm and extend RNAseq data and gene targets related to 5-nitroimidazole resistance. RESULTS/ANTICIPATED RESULTS: RNAseq identified key DEGs in MTZ-resistant vs. sensitive isolates. DEGs from MTZ-resistant isolates included those involved in metabolic pathways relevant to 5-nitroimidazole resistance such as energy production (glycolytic enzymes) and oxygen-scavenging (thioredoxin). Other DEGs included those encoding transcription factors (MYB DNA-binding protein), ribosomal proteins (30S, 40S, 50S, 60S), protein kinases (CAMK, ser/thr, CMGC), Ankyrin repeat proteins, surface proteins (Surface antigen BspA-like) and various uncharacterized hypothetical proteins. RT-qPCR experiments confirmed reduced expression of genes encoding ferredoxin (drug activation) and flavin reductase 1 (oxygen scavenging) in MTZ-resistant T. vaginalis isolates as compared to MTZ-sensitive isolates. DISCUSSION/SIGNIFICANCE: In this study, we identified several DEGs in resistant T. vaginalis isolates. Further studies with large number of isolates representing a broad range of MTZ-susceptibility patterns are needed to identify genes that may represent new targets for future drug development.